2011
DOI: 10.1007/s00449-011-0664-2
|View full text |Cite
|
Sign up to set email alerts
|

Biobutanol production from rice bran and de-oiled rice bran by Clostridium saccharoperbutylacetonicum N1-4

Abstract: Rice bran (RB) and de-oiled rice bran (DRB) have been treated and used as the carbon source in acetone-butanol-ethanol (ABE) production using Clostridium saccharoperbutylacetonicum N1-4. The results showed that pretreated DRB produced more ABE than pretreated RB. Dilute sulfuric acid was the most suitable treatment method among the various pretreatment methods that were applied. The highest ABE obtained was 12.13 g/L, including 7.72 g/L of biobutanol, from sulfuric acid. The enzymatic hydrolysate of DRB (ESADR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(37 citation statements)
references
References 30 publications
2
33
0
2
Order By: Relevance
“…In this regard, Al-Shorgani et al (2011) pretreated rice bran with 1% (v/v) H2SO4 and 1% (v/v) HCl for further utilization in the ABE process. The pretreatment results revealed that when H2SO4 and HCl were used, the concentrations of total sugar recovered from pretreated rice bran were 31.43 g/L and 9.7 g/L, respectively.…”
Section: Abe Fermentation Using Acid-pretreated Pkcmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, Al-Shorgani et al (2011) pretreated rice bran with 1% (v/v) H2SO4 and 1% (v/v) HCl for further utilization in the ABE process. The pretreatment results revealed that when H2SO4 and HCl were used, the concentrations of total sugar recovered from pretreated rice bran were 31.43 g/L and 9.7 g/L, respectively.…”
Section: Abe Fermentation Using Acid-pretreated Pkcmentioning
confidence: 99%
“…Recently, many studies have focused on finding alternative inexpensive and non-food-based substrates. In the past few years, many studies have focused on the use of lignocellulose materials, such as palm oil mill effluent (Kalil et al 2003), corn stove and barley straw (Qureshi et al 2014), rice bran, and deoiled rice bran (Al-Shorgani et al 2011), as feedstocks for the ABE fermentation process.…”
Section: Introductionmentioning
confidence: 99%
“…At the moment, agricultural products and wastes such as sugar canes, cassavas, rice straws, corncobs, corn, wheat straw, sweet sorghum, sweet cheese whey, rice bran, date fruit, oil palm trunk sap, and palm oil mill effluent are used as raw materials for the production of butanol [3][4][5][6][7][8][9][10][11][12][13][14]. Therefore, lignocelluloses, substances commonly found in agricultural wastes, appear to be a feasible resource compare to agricultural products which are used as foods.…”
Section: Introductionmentioning
confidence: 99%
“…Etanol é o biocombustível mais usado no mundo, no entanto, o butanol apresenta melhores propriedades, principalmente a energia específica, que é significativamente maior que a do etanol (Al-Shorgani et al, 2012). O biobutanol pode ser atrativo, ainda, para substituição do uso de gasolina, já que, apresenta grande similaridade com este combustível fóssil (Mayank et al, 2013).…”
Section: Introductionunclassified